Sensory quantitative descriptive analysis of African slimy okra (Abelmoschus esculentus) preparations and its correlation with instrumental parameters. Issue 3 (22nd January 2021) - Savouré, Timoty; Dornier, Manuel; Maraval, Isabelle; Collignan, Antoine
Abstract: Okra ( Abelmoschus esculentus ) is one of the ingredients used in traditional West and Central African gastronomy because of the slimy texture it gives to sauces, soups and stews. However, in the literature, the definition of "sliminess" is unclear, the textural perception of these slimy preparations has not been described, and the possibility of measuring the textural quality of these sauces instrumentally has not been established. This study therefore aims (a) to identify the sensory attributes adapted to describe the texture of these slimy sauces and (b) to verify that the instrumental measurements adapted to characterize the rheology and texture of these sauces are well correlated to these attributes. Nine okra sauces were prepared by varying their formulation and the preparation process. A quantitative descriptive sensory analysis and a ranking test were carried out with a trained panel of 16 panelists. The texture of the okra‐based slimy sauces prepared can be described using 11 attributes referring to their consistency and to their adhesive, elastic, elongation and functional properties. Results showed that sliminess is a complex textural property resulting from the combined perception of stringiness and viscosity of semi‐solid matrices. Therefore, it is not possible to correctly predict the sensory perception of sliminess with a single instrumental measurement. However, measuring their consistency index K and their stringiness is necessary and sufficient to characterize the texture of these sauces and to predict the sensory perception of their consistency and elongational properties. Abstract : Measuring consistency index K and stringiness is sufficient to characterize the texture and predict perception of slimy preparations. Sliminess is a complex textural property resulting from the combined perception of stringiness and viscosity of semi‐solid matrices.